THE ROLE OF RED-SLIPPED POTTERY IN ESTABLISHING THE CHRONOLOGICAL AGE OF THE CITY OF KOKAND - Priniyazov J. A. (TARIXIY TADQIQOTLAR, 2026)
This article presents a detailed analysis of the scientific significance of redslipped pottery in establishing the chronological age of the city of Kokand, drawing upon archaeological reports and existing scholarly literature. The study first examines historical sources that mention Kokand as an early settlement and highlight its emergence as a center located at the crossroads of caravan routes. It then analyzes archaeological investigations conducted at the Moyi Muborak and Tepakurgan sites, focusing on the chronological features of red-slipped ceramic assemblages recovered from stratified layers. These vessels display notable parallels with assemblages from ancient Eski Axsi in terms of their shapes, slip quality, and technological characteristics. The results demonstrate that red-slipped pottery provides significant evidence for the existence of early ceramic production in the Kokand region.